Estimating cigarette tax avoidance and evasion: evidence from a national sample of littered packs. (3rd October 2016) - Barker, Dianne C; Wang, Shu; Merriman, David; Crosby, Andrew; Resnick, Elissa A; Chaloupka, Frank J
Abstract : Introduction: A number of recent studies document the proportion of all cigarette packs that are 'contraband' using discarded packs to measure tax avoidance and evasion, which we call tax non-compliance. To date, academic studies using discarded packs focused on relatively small geographical areas such as a city or a neighbourhood. Methods: We visited 160 communities across 38 US states in 2012 and collected data from littered cigarette packs as part of the State and Community Tobacco Control (SCTC) Research Initiative and the Bridging the Gap Community Obesity Measures Project (BTG-COMP). Data collectors were trained in a previously tested littered pack data collection protocol. Results: Field teams collected 2116 packs with cellophane across 132 communities. We estimate a national tax non-compliance rate of 18.5% with considerable variation across regions. Suburban areas had lower non-compliance than urban areas as well as areas with high and low median household income areas compared with middle income areas. Discussion: We present the first academic national study of tax non-compliance using littered cigarette packs. We demonstrate the feasibility of meaningful large-scale data collection using this methodology and document considerable variation in tax non-compliance across areas, suggesting that both policy differences and geography may be important in control of illicit tobacco use. Given the geography of open borders among countries with varying tax rates, this simple methodology may be appropriate to estimate tax non-compliance in countries that use tax stamps or other pack markings, such as health warnings.